Regulating the working conditions of platform work: What can we learn from EU member states? - Oscar Guinea; Elena Sisto; Oscar du Roy (European Centre for International Political Economy (ECIPE), 2024)
This Policy Brief offers a comprehensive evaluation and comparison of the regulatory frameworks governing platform work in four European countries. The comparative analysis draws upon research conducted by the OECD and the World Economic Forum (WEF) on the principles of good regulation. Adapting this research to the context of digital platforms, three key principles for assessing the regulation of working conditions on these platforms were identified: (i) the consistency with the policy objective of improving the working conditions of platform workers; (ii) the feasibility of implementing the regulatory requirements; (iii) the presence of regulatory requirements; (iii) the presence of regulatory dialogue and appeal mechanisms.
Keywords: 330; Working conditions; Digital platform; Digital economy; Regulation; Labor law; Comparison; Spain; France; Estonia; Greece; EU countries; Arbeitsbedingungen; Digitale Plattform; Digitalökonomie; Regulierung; Arbeitsrecht; Vergleich; Spanien; Frankreich; Estland; Griechenland; EU-Staaten